2017
DOI: 10.1080/09298215.2017.1355394
|View full text |Cite
|
Sign up to set email alerts
|

The Tight-interlocked Rhythm Section: Production and Perception of Synchronisation in Jazz Trio Performance

Abstract: This study investigates the production and perception of timing, synchronisation and dynamics in jazz trio performances. In a production experiment, six trio combinations of one saxophonist, two bassists, and three drummers were recorded while they performed three popular jazz songs. Onset timing and dynamics of each performer were extracted and analysed. Results showed that the tempo was significantly influenced by the timing of the drummers and all performers showed higher temporal precision on the backbeats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 40 publications
(67 reference statements)
1
30
0
Order By: Relevance
“…We further obtained some evidence that the groove ratings of stimuli with microtiming that arises in professional performance are on par with those elicited by stimuli with quantized timing (Senn et al, 2016 ) and that it is not necessarily the quantized stimuli that motivate the most intense body movement in listeners (Kilchenmann and Senn, 2015 ). Finally, Hofmann et al ( 2017 ) suggested that tight microtiming patterns are preferred by listeners, compared to larger microtiming magnitudes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We further obtained some evidence that the groove ratings of stimuli with microtiming that arises in professional performance are on par with those elicited by stimuli with quantized timing (Senn et al, 2016 ) and that it is not necessarily the quantized stimuli that motivate the most intense body movement in listeners (Kilchenmann and Senn, 2015 ). Finally, Hofmann et al ( 2017 ) suggested that tight microtiming patterns are preferred by listeners, compared to larger microtiming magnitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Another yet unchartered territory in groove studies is related to the variability of microtiming patterns across the time of a performance. In the past, average microtiming variation profiles have been extracted from performed music (see examples in Fujii et al, 2011 ; Kilchenmann and Senn, 2011 , 2015 ; Naveda et al, 2011 ; Hellmer and Madison, 2015 ; Hofmann et al, 2017 ). These patterns may well represent a systematic aspect of microtiming in a certain style or context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet others claimed that expert performance microtiming did not diminish entrainment or pleasure, but exaggerating the microtiming pattern had a negative effect on groove [ 67 , 68 ]. One recent study [ 69 ] found that listeners preferred stimuli with small expert performance microtiming deviations to stimuli with quantised timing. In summary, there are conflicting findings concerning the influence of microtiming on groove.…”
Section: Introductionmentioning
confidence: 99%
“…Expertise : Listeners’ musical expertise was studied under the assumption that music expert listeners would be more sensitive to musical phenomena (like microtiming deviations or syncopation) than listeners with less expertise. Some studies concluded that listeners’ expertise did not influence the experience of groove within the context of their investigations [ 5 , 62 , 64 , 69 , 73 ]. Others found that musical expertise did have a moderating effect on groove: higher musical expertise was associated with a stronger effect of microtiming on the groove experience [ 65 , 67 , 68 ] or with physiological reactions linked to groove [ 80 ].…”
Section: Introductionmentioning
confidence: 99%